Effects of baseline problematic alcohol and drug use on internet-based cognitive behavioral therapy outcomes for depression, panic disorder and social anxiety disorder. - Mikael Gajecki (Public Library of Science (PLoS), 2014)
Purpose Patients' problematic substance use prevalence and effects were explored in relation to internet-based cognitive behavioral therapy (ICBT) outcomes for depression, panic disorder and social anxiety disorder. Methods At baseline and treatment conclusion, 1601 ICBT patients were assessed with self-rated measures for alcohol and drug use (AUDIT/DUDIT), depressive symptoms (MADRS-S), panic disorder symptoms (PDSS-SR) and social anxiety symptoms (LSAS-SR). Results Problematic substance use (AUDIT ≥ 8 for men, ≥ 6 for women; DUDIT ≥ 1) occurred among 32.4% of the patients; 24.1% only alcohol, 4.6% only drugs, and 3.7% combined alcohol and drug use. Hazardous alcohol use and probable alcohol dependence negatively affected panic disorder outcomes, and hazardous drug use led to worse social anxiety outcomes. Depression outcomes were not affected by substance use. Treatment adherence was negatively affected by problematic drug use among men and 25-34 year olds; combined substance use negatively affected adherence for women and 35-64 year olds. Conclusion Problematic substance use does not preclude ICBT treatment but can worsen outcomes, particularly problematic alcohol use for panic disorder patients and hazardous drug use for social anxiety patients. ICBT clinicians should exercise particular caution when treating men and younger patients with problematic drug use, and women or older patients with combined substance use.